Oral administration of linoleic acid immediately before glucose load ameliorates postprandial hyperglycemia - Yamamoto, Yuta; Narumi, Katsuya; Yamagishi, Naoko; Nishi, Toshio; Ito, Takao; Iseki, Ken; Kobayashi, Masaki; Kanai, Yoshimitsu (Frontiers in Pharmacology, 2023)
Introduction Fatty acids are a major nutrient in dietary fat, some of which are ligands of long-chain fatty acid receptors, including G-protein-coupled receptor (GPR) 40 and GPR120. Pretreatment with GPR40 agonists enhanced the secretion of insulin in response to elevating blood glucose levels after glucose load in a diabetes model, but pretreatment with GPR120 agonist did not ameliorate postprandial hyperglycemia. This study examined whether oral administration of linoleic acid (LA), a GPR40 and GPR120 agonist, immediately before glucose load would affect the elevation of postprandial blood glucose levels in rats. Methods Male rats and rats with type 1 diabetes administered streptozocin were orally administered LA, trilinolein, α-linolenic acid (α-LA), oleic acid, TAK-875, or TUG-891 immediately before glucose load. Blood glucose levels were measured before, then 15, 30, 60 and 120 min after glucose load. CACO-2 cells were used to measure the uptake of [14C] α-MDG for 30 min with or without LA. Gastric content from rats administered LA was collected 15 and 30 min after glucose load, and blood samples were collected for measurement of glucagon-like peptide 1 (GLP-1) and cholecystokinin concentrations. Results The elevation of postprandial blood glucose levels was slowed by LA but not by trilinolein in rats without promotion of insulin secretion, and this effect was also observed in rats with type 1 diabetes. The uptake of α-MDG, an SGLT-specific substrate, was, however, not inhibited by LA. Gastric emptying was slowed by LA 15 min after glucose load, and GLP-1, but not cholecystokinin, level was elevated by LA 15 min after glucose load.TUG-891, a GPR120 agonist, ameliorated postprandial hyperglycemia but TAK-875, a GPR40 agonist, did not. Pretreatment with AH7614, a GPR120 antagonist, partially canceled the improvement of postprandial hyperglycemia induced by LA. α-LA, which has high affinity with GPR120 as well as LA, slowed the elevation of postprandial blood glucose levels, but oleic acid, which has lower affinity with GPR120 than LA, did not. Conclusion Oral administration of LA immediately after glucose load ameliorated postprandial hyperglycemia due to slowing of gastric emptying via promotion of GLP-1 secretion. The mechanisms may be associated with GPR120 pathway.